Interobserver Variability in Scoring Liver Biopsies with a Diagnosis of Alcoholic Hepatitis. (28th July 2017) - Horvath, Bela; Allende, Daniela; Xie, Hao; Guirguis, John; Jeung, Jennifer; Lapinski, James; Patil, Deepa; McCullough, Arthur J.; Dasarathy, Srinivasan; Liu, Xiuli
Abstract : Background: Alcoholic hepatitis (AH) is one of the most severe forms of alcoholic liver disease. Recently, a histologic scoring system for predicting prognosis in this patient cohort was proposed as Alcoholic Hepatitis Histologic Score (AHHS). We aimed to assess interobserver variability in recognizing histologic features of AH and the effect of this variability on the proposed AHHS categories. Methods: Hematoxylin–eosin‐ and trichrome‐stained slides from 32 patients diagnosed with AH with liver biopsies within 1 month of presentation (2000 to 2015) were reviewed by 5 pathologists including 3 liver pathologists and 2 gastrointestinal (GI) pathologists masked to the clinical findings or outcome. Histologic features of AH were assessed, the AHHS was calculated, and an AHHS category (mild, moderate, severe) was assigned. The Fleiss' kappa coefficient (κ) analysis was performed to determine the interobserver agreement. Results: A slight‐to‐moderate level of interobserver agreement existed among 5 reviewers on histopathologic features of AH with κ value ranging from 0.20 (95% confidence interval (CI): 0.03 to 0.46, megamitochondria) to 0.52 [95% CI: 0.40 to 0.68, polymorphonuclear leukocyte (PMN) infiltration]. There was only a fair level of agreement in assigning AHHS category (κ = 0.33, 95% CI: 0.20 to 0.51). While overall fibrosis and neutrophilic inflammation were comparably evaluated by 3 liver pathologists and 2 GI pathologists, bilirubinostasis and megamitochondria were more consistently diagnosed by liver pathologists. Overall, 18 of 32 (56%) were uniformly assigned to an AHHS category by all liver pathologists with a κ value of 0.40 (95% CI: 0.22 to 0.60). Conclusions: In general, features of AH can be recognized with a slight‐to‐moderate level of interobserver agreement and there was fair interobserver agreement on assigning an AHHS category. Significant interobserver variability among pathologists revealed by the current study can limit its usefulness in everyday clinical practice. Abstract : Liver biopsy plays a significant role in diagnosing alcoholic hepatitis (AH). Morphologic features of AH include hepatocyte ballooning, Mallory hyalines, and neutrophilic inflammation. A recently proposed Alcoholic Hepatitis Histologic Score (AHHS) was reported to be predictive of 90‐day mortality. Our study showed that there was only fair interobserver agreement on assigning an AHHS category. Our finding of significant interobserver variability among pathologists in assigning an AHHS category can limit its usefulness in everyday clinical practice.